Multiobjective control architecture to estimate optimal set points for user comfort and energy saving in buildings. (April 2020) - Martell, M.; Rodríguez, F.; Castilla, M.; Berenguel, M.
Abstract: Temperature control in buildings is usually driven by energy conservation although the occupants' comfort is also important considering its impact on productivity and health. However, energy efficiency and comfort are opposing objectives and therefore this type of problem can be resolved by means of a multiobjective optimization approach. The simulations we carried out indicate that set points optimization has the potential to reduce energy consumption in the order of 10% while also providing a comfortable work environment for the occupants. Highlights: This work presents the procedure to implement a set-points optimizer for a building. Two main objectives are considered: users' comfort and energy consumption. The proposed optimizer has been merged into a multilevel hierarchical control system. The performance of the optimizer has been tested for typical days from March to July. The proposed optimizer is able to estimate set-points to guarantee users' comfort. Simultaneously, the proposed optimizer can increase energy savings between 7 to 19%.